Factors influencing Needle Pricks Stick injuries among Dental Health training Students. A Case Study at International Paramedical School, Maya Wakiso District. - Lwanga Othieno, Charles (Student's Journal of Health Research Africa, 2022)
Background: NSI is the wound or cut caused by the needles that unintentionally tear/puncture the skin that may result in exposure to contaminated blood and body fluids. Nursing workers are at high risk of exposure to Bloodborne germs i.e. HIV and HBV. The specific objectives were; to assess the knowledge of dental training students, to assess for factors influencing needle stick injuries among dental training students, and to determine the prevalence of needle stick injuries among dental training students at International Paramedical School, Maya, Wakiso District. Methodology: This was a descriptive and cross-sectional study employing both qualitative and quantitative methods of data collection using structured questionnaires. A sample size of 80 participants was used. Data was analyzed and presented in form of frequency tables, pie charts, and bar graphs. Results: The study findings were as follows; 76.7% knew what a needle stick injury is, 57.8% agreed with the fact that needle prick injuries are a danger to health, and HIV and Hepatitis B were the most commonly known diseases that can be transmitted by needle prick injuries and 17.5% had ever learned about standard precautions for needle stick injuries.76(95%) had ever had needle stick injuries, most males (61.3%) had needle sticks injury Conclusion: there was fair knowledge, which still needs to be improved, males get more NSIs compared to females, and most injuries are got during recapping of needles and suturing. Recommendation: The students should report every case of needle stick injuries so that appropriate actions can be taken.